SPEECH FUNCTION IN JOKOWI’S SPEECHES - Teguh K. I Tarigan; Muhammad Natsir (LINGUISTICA, 2014)
ABSTRACT This study deals with Speech Function in Jokowi’s Speeches. The objectives of this study are to find out the types of Speech Function, the most dominant type of Speech Function used, and the meaning of the dominantly used. The research on this thesis was carried by using descriptive qualitative. The data were taken from 4 speeches of Jokowi in English. The data were analyzed and classified into four types of speech functions in the procedures namely Statement, Question, Offer, and Command. There are 116 speech functions from 4 speeches of Jokowi. The findings indicated thatthere are Statement 88 (75,86%), Question 11 (9,48%), Command 17 (14,66%), and there is no Offer in Jokowi’s Speeches (0%). Statement as the most dominant type of speech function is used in Jokowi’s speeches it’s mean give or state information, the way of the speaker to deliver the information about the Jakarta city’s problem and how to solve it, the speaker’s planning for Jakarta, and give thanks for the audience in Jakarta Anniversary to the audience by using statement.     Key words: Speech Function, Statement, Question, Offer, Command